Interactive effects of altitude, microclimate and shading system on coffee leaf rust - Liebig, Theresa Ines; Ribeyre, Fabienne; Läderach, Peter R.D.; Poehling, Hans-Michael; Asten, Piet J.A. van; Avelino, Jacques (Informa UK Limited, 2019)
Shade effects on coffee diseases are ambiguous because they vary depending on the season and environment. Using Coffee Leaf Rust (CLR) as an example, we demonstrate relationships between the environment and shading systems and their effects on disease intensity. We characterized seasonal variations in microclimate and CLR incidence across different altitudes and shading systems, and integrated effects between the environment, shading systems, microclimate and CLR into a piecewise structural equation model. The diurnal temperature range was higher in unshaded systems, but differences decreased with altitude. Humidity related indicators in shaded systems decreased with altitude. At mid and high altitudes, high CLR incidence occurred in the shading system showing a low diurnal temperature range and a high dew point temperature. Our study demonstrates how microclimatic indicators vary as a function of the season, altitude and the coffee shading system, and how this in turn is related to CLR.